Sporadic aniridia and Wilm’s tumor – a case report and review of recommendation for diagnostic approach in WAGR’s Syndrome - Orawiec, Beata; Młynarski, Wojciech; Budzińska-Mikurenda, Małgorzata; Grałek, Mirosława; Szewczyk-Zalewska, Beata; Niwald, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
The current paper presents a case of 14 months old girl with WAGR’s syndrome. This syndrome is a genetic disorder characterized by the deletion at 11p13 locus which gives clinical presentation of aniridia, Wilms’ tumor, genitourinary anomalies and mental retardation. Although WAGR’s syndrome is a rare disorder, knowledge of its presentation is helpful in early diagnosis of nephroblastoma and may have impact on clinical outcome of the patient. Since aniridia may be the first symptom of WAGR’s syndrome, it is ecommended that all neonates with aniridia need to be screened for deletion of WT1 on chromosome 11p13. These with deletions should be monitored regularly for tumor development.